NeuroPredict: study of the predictive value of ABCB1 genetic polymorphisms and associated clinical factors in chronic chemotherapy-induced peripheral neuropathy (CIPN) - Vargas-Aliaga, Alicia; De la Haba, María; Contreras, María José; Morales Estevez, Cristina; Porras, Ignacio; Cano, María Teresa; Pulido, Gema; Gómez, María Auxiliadora; Flores-Paco, Pablo; Juan, De La Haba-Rodriguez; Aranda, Enrique (Frontiers in Pharmacology, 2024)
Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a common entity (30-40%) and can significantly limit the quality of life of patients, especially those that persist for more than six months after treatment (chronic neuropathy). Studies have shown a possible association between the presence of genetic polymorphisms in ABCB1 and the development of acute CIPN, although this relationship with chronic CIPN remains unexplored. This is an analytical observational case-control study defined by the presence (cases) or absence (controls) of CIPN at 6 months after the end of the neurotoxic drug. Our aim is to demonstrate whether these ABCB1 polymorphisms also influence the chronification of this toxicity, as well as the clinical factors that can help us to predict it. Methods: The study included 152 patients treated with tri-weekly oxaliplatin (O) or weekly paclitaxel (P); 86 cases and 66 controls. Clinical and analytical parameters were analysed including the study of ABCB1 genetic polymorphisms in a blood sample. Results: ABCB1 genetic polymorphisms C1236T (rs1128503) and C3435T (rs1045642) are associated with the development of chronic CIPN in patients treated with P. No differences were found in patients treated with O. Other predictive factors to be considered in the development of this toxicity are age > 60 years, BMI ³ 30, toxic habits and cardiovascular risk factors. Conclusion: CIPN is a common and understudied toxicity, despite being a limiting factor in the quality of life of many patients. As described in acute CIPN, our study demonstrates the relationship between chronic neuropathy and being a carrier of specific polymorphisms (C1236T and C3435T) of the ABCB1 gene in patients treated with P. In addition, there are modifiable factors (obesity, smoking, or alcohol) that may influence its development. Further prospective studies are needed to investigate genetic and clinical modifiable factors predisposing to CIPPN to develop prevention and treatment strategies.